Montale and the Occasions of Poetry - Huffman, Claire de C. L. (Book collections on Project MUSE., 2014)
The six overlapping studies that make up this book on the poetry of Eugenio Montale analyze a large number of individual poems and, with Le occasioni (1939) as a point of reference, show how they shape and are shaped by changes and continuities that extend from the earliest poems of Ossi di seppia (1925) to the notoriously difficult poems in his culminating achievement, La bufera (1956). Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist.